Pandemic and Teacher’s Perceptions About Emergency Remote Teaching: The Uruguayan Case - Vaillant, Denise (2022)
Introduction. This article presents the results of an international research study for the Uruguayan case. The research analyzed teachers’ perceptions of emergency remote teaching in a national context. This context had two distinctive characteristics: universal access to technological resources for teaching due to the national coverage of the Ceibal Plan and online educational continuity. Objective: The study aimed to know the changes in teaching processes due to the COVID-19 health emergency. Method. The study was based on a mixed descriptive design that integrated quantitative and qualitative data. The information was collected through a self-administered digital survey applied to 470 teachers between May and June 2020; they were working at different teaching levels, from early education to university. Results. Even in a country like Uruguay with high educational connectivity, the suspension of in-person classes due to COVID-19 caused tensions and challenges at the work, pedagogy, and technology levels. There was a negative impact on occupational health and teacher stress. In addition, problems of low appropriation and pedagogical use of technologies the teaching staff experienced were registered. Discussion. One of the significant challenges the teaching staff pointed out is constructing new pedagogical formats to improve educational results with equity.